DEVELOPMENT OF STUDENTS’ COMMUNICATIVE CULTURE VIA ONLINE FOREIGN LANGUAGE INTERACTION - Klets, Tatyana; Nikiforova, Elena; Presnyakova, Nadezhda; Starovoitova, Maria (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article focuses on the use of digital technologies in the foreign language learning process and the formation of students’ communicative culture via online interaction. The issue discussed in this paper is very urgent because nowadays digital technologies are viewed as a comprehensive means of teaching a foreign language in a higher educational institution. General cultural competency and communicative culture, particularly, are considered as an integrative quality of a specialist concerning his potential for self-realization in his future career. In this regard, the actual problem is the methodically correct organisation of the educational process for students’ cultural development on the basis of digital technologies. The research is aimed at the theoretical substantiation of pedagogical effectiveness of the organization of online training in foreign language communication as a condition for the formation of the communicative culture of undergraduate students as well as the generalization of the results of experimental training. To verify the productivity of digital resources in foreign language training and cultural development of university students the authors conducted a pedagogical experiment using theoretical and empirical methods of scientific research. The results of the experiment proved the effectiveness of online teaching in mastering communicative culture components.